Remaining shelf-life prediction of squid using handheld Vis/NIR spectroscopy and ensemble learning - Miao, Xin; Sun, Yajie; Tong, Anyi; Bao, Wansheng; Liu, Chichao; Cao, Shouqi; Chen, Xinjun (International Journal of Agricultural and Biological Engineering, 2026)
To address the limitations of traditional squid freshness assessment, which relies on destructive physicochemical indicators and neglects anatomical spatial heterogeneity—thereby compromising on-site accuracy—this study developed an integrated handheld visible and near-infrared (Vis-NIR) spectroscopy system combined with intelligent algorithms. A multi-scale decomposition of spectral signals (450-950 nm) was innovatively performed using Discrete Wavelet Transform (DWT) to extract energy spectrum features. By integrating Isolation Forest for outlier rejection and a Stacked Ensemble Learning framework (Stacking: base=Ridge/RF/HGBR, meta=GBR), a robust prediction model for storage time was constructed. The experimental results demonstrated that the proposed model achieved an excellent coefficient of determination (R2=0.9528), a Root Mean Square Error (RMSE=0.6566 d), and a Residual Prediction Deviation (RPD=4.60) on the validation set, with uniformly distributed residuals cross-verified by the Breusch–Pagan test (p=0.6944). Weibull kinetic modeling revealed distinct degradation patterns across anatomical sites; specifically, the abdominal region exhibited a maximum shape parameter (=1.787) and a massive Akaike Information Criterion advantage (AIC=490.6) over the first-order kinetic paradigm, indicating an accelerating, self-catalytic quality degradation profile driven by endogenous visceral enzymes. Finally, the real-time predicted storage time was successfully coupled with local Weibull parameters to output probabilistic Remaining Shelf Life (RSL) profiles via Kernel Density Estimation (KDE), which establishes a proactive digital traceability pipeline for precision grading and dynamic inventory management of high-value marine aquatic products. Key words: squid freshness; handheld spectrometer; spatial heterogeneity; stacked ensemble learning; kinetic modeling; remaining shelf life (RSL) DOI: 10.25165/j.ijabe.20261904.10501 Citation: Miao X, Sun Y J, Tong A Y, Bao W S, Liu C C, Cao S Q, et al. Remaining shelf-life prediction of squid using handheld Vis/NIR spectroscopy and ensemble learning. Int J Agric & Biol Eng, 2026; 19(4): 338–346.